Energy cost and game dynamics in soccer: comparing sided games and repeated sprint training - Akilveren, E.; Sahan, A.; Özdogan, E. Ç. (BMC Sports Science, Medicine and Rehabilitation, 2025)
Background This study aims to propose an alternative solution for determining the optimal training load to meet the high physiological demands of football, encompassing both metabolic and locomotor loads. To this end, two different formats, repetitive sprint training (RST) and sided games (SGs), were evaluated in terms of energy cost (EC), and their similarities were revealed.